The Dehumanizing American Dream in David Mamet’s Glengarry Glen Ross - Sepehrmanesh, Mehdi; Dehghani, Ehsan (k@ta: A Biannual Publication on the Study of Language and Literature, 2014)
The American Dream is a recurrent theme in American literature. In this response, this paper is an attempt to expose the destructive effects of the dream on the human spirit. It is also shown, through the analysis of David Mamet‟s glengarry Glen Ross, that despite the promise of the dream it contains many contradictions. Beneath the seeming simple surface of the play lies a deep current of meanings that reflect the calamities of modern American life, and in a broader sense, the modern world. This article indicates how capitalism inculcates ideologies in the mind of individuals in order to facilitate the exploiting process and unquestioning subordination. Ragged individualism, for instance, as the most prominent of these ideologies, disrupts all communal bonds and even exceeds to the disintegration of friendship and family life.